2 − x + 4 − 3 x 2 − x − 4 − 3 x = 6 − 5 x + 8 − 7 x 6 − 5 x − 8 − 7 x , x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
All the rest of the solutions in one way or another give you an imaginary solution; therefore, the answer has to be 1.
Problem Loading...
Note Loading...
Set Loading...
Use componendo-dividendo to get : 4 − 3 x 2 − x = 8 − 7 x 6 − 5 x Square both sides and cross multiply ( 4 − 3 x ) ( 6 − 5 x ) = ( 2 − x ) ( 8 − 7 x ) ⇒ 2 4 − 2 0 x − 1 8 x + 1 5 x 2 = 1 6 − 1 4 x − 8 x + 7 x 2 ⇒ 2 4 − 3 8 x + 1 5 x 2 − 1 6 + 2 2 x − 7 x 2 = 0 ⇒ 8 x 2 − 1 6 x + 8 = 0 ⇒ 8 ( x 2 − 2 x + 1 ) = 0 ⇒ x 2 − 2 x + 1 = 0 ⇒ ( x − 1 ) 2 = 0 ⇒ x = 1